2017
DOI: 10.1002/psp4.12253
|View full text |Cite
|
Sign up to set email alerts
|

Network‐Wide Screen Identifies Variation of Novel Precise On‐Module Targets Using Conformational Modudaoism

Abstract: Modular targeting is promising in drug research at the network level, but it is challenging to quantificationally identify the precise on‐modules. Based on a proposed Modudaoism (MD), we defined conserved MD (MDc) and varied MD (MDv) to quantitatively evaluate the conformational and energy variations of modules, and thereby identify the conserved and discrepant allosteric modules (AMs). Compared to the Zsummary, MDc/MDv got an optimized result of module preserved ratio and modular structure. In the mice anti‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Several studies have attempted to identify the module biomarker for complex diseases or drug targets ( 9 11 ). Under different drugs treatment, the gene co-expression relationship could be changed and manifest as the intramodular rewiring, so we can identify the modular targets of drugs based on the condition of specific modular configuration ( 40 ). Based on the functional enrichment analysis, we found that the 4 identified BJ Add-modules were closely associated with CI.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have attempted to identify the module biomarker for complex diseases or drug targets ( 9 11 ). Under different drugs treatment, the gene co-expression relationship could be changed and manifest as the intramodular rewiring, so we can identify the modular targets of drugs based on the condition of specific modular configuration ( 40 ). Based on the functional enrichment analysis, we found that the 4 identified BJ Add-modules were closely associated with CI.…”
Section: Discussionmentioning
confidence: 99%